Durio connatus (Malvaceae), a new species from Kalimantan, Indonesia - Priyanti, Priyanti; Chikmawati, Tatik; Sobir, Sobir; Hartana, Alex (Phytotaxa, 2016)
Durio connatus is described and illustrated as a new species for the first time. This species is similar to D. kutejensis, but has four unique characters, viz. shorter petals, stamens fasciculate in five phalanges with filaments connate basally, stamens caduceus, falling easily from the petals and sepals, and fruit opening easily before falling to the ground.